Methodology and Axiological Content of Values ​​Education Programs (Foro de Educacion, 2016)
Values education is a learning process that enhances the axiological development of people. From this point of view, the models proposed by Kohlberg (1976) and Molina (2012) provide the basis for planning education programs in values. In the present paper is reviewed historical evolution of the most important in the development of education programs in values theoretical and methodological models. To this end it has carried out a careful review of the relevant scientific literature databases (PsycINFO, Psicodoc, ERIC, EBSCO, Social Services and Abstract Web of Knowledge). The result allows comparisons between different theoretical models and identify the strengths and weaknesses of each of these points, as well as exposure of the main methodological elements involved in values education. Thus, they describe the properties and components of judgment for the selection of the values considering the recipients of educational action.